Effects of regenerator structure on performance of free piston stirling engine (FPSE) - Kim, Byung Gyun; Park, Won-Shik; Koo, Bon-Gil; Park, Suhan (Journal of mechanical science and technology, 2018)
This study explains the construction and use of SAGE, a commercial analysis program used in the development of Stirling engines, and describes its applications. The free piston Stirling engine (FPSE), which is a type of Stirling engine, eliminates excessive mechanical parts to solve the disadvantages of conventional Stirling engines (weight, size, and mechanical loss of connecting parts for reciprocating motion) and connecting springs to each piston vibration system. In this paper, we briefly describe the SAGE program and investigate the effect of numerical variations of the analytical elements (porosity, mesh diameter, regenerator diameter) of the regenerator on the performance of FPSE using the basic model embedded in the program. We also apply this model to future FPSE development.